2017
DOI: 10.5206/eei.v27i1.7748
|View full text |Cite
|
Sign up to set email alerts
|

Faculty Preparedness to Teach Students with Learning Disabilities: Developing an Instrument to Assess Faculty Perceptions

Abstract: Despite increasing rates of entry, students with learning disabilities (LD) continue to face barriers to completing post-secondary education. Faculty attitudes and knowledge are important factors in supporting students with LD, yet little is known about faculty preparation. No valid, reliable, easy-to-administer inventory exists to assess the perceptions of faculty about their preparedness for the task of teaching students with LD. The Faculty Preparedness Questionnaire (FPQ) was developed to measure faculty p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 15 publications
1
13
1
Order By: Relevance
“…There is a substantial discrepancy, however, between these findings and what students with disabilities report on this matter (e.g., Dowrick et al, 2005). Other scholars have found that attitudes do not always predict educational practices (Hansen et al, 2017;Hansen & Dawson, 2020). In other words, there may also be inconsistencies between reported attitudes and behaviour.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…There is a substantial discrepancy, however, between these findings and what students with disabilities report on this matter (e.g., Dowrick et al, 2005). Other scholars have found that attitudes do not always predict educational practices (Hansen et al, 2017;Hansen & Dawson, 2020). In other words, there may also be inconsistencies between reported attitudes and behaviour.…”
Section: Discussionmentioning
confidence: 93%
“…Theoretically, a faculty's willingness to accommodate or implement inclusive education strategies should be correlated with their attitudes toward disability. In fact, measures of educators' attitudes toward disability often include items and/or subscales related to these educational practices (Hansen et al, 2017;Lombardi & Murray, 2011;Freer, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The current study builds on previous research by Hansen, Dawson, & Specht (2017) where researchers developed the Faculty Preparedness Questionnaire (FPQ) to measure faculty attitudes and knowledge as components of their preparedness to teach students with LDs. This new instrument consists of 17 statements rated on a 6-point Likert scale; 9 comprise the knowledge subscale, and 8 comprise the attitude subscale.…”
Section: Faculty Perceptions Of Students With Ldsmentioning
confidence: 99%